(untitled) - Eves, Howard Whitley ([Washington, D.C.], 2003)
For many years, famed mathematics historian and master teacher Howard Eves collected stories and anecdotes about mathematics and mathematicians, gathering them together in six Mathematical Circles books. Thousands of teachers of mathematics have read these stories and anecdotes for their own enjoyment and used them in the classroom - to add entertainment, to introduce a human element, to inspire the student, and to forge some links of cultural history. All six of the Mathematical Circles books have been reissued as a three-volume edition. This three-volume set is a must for all who enjoy the mathematical enterprise, especially those who appreciate the human and cultural aspects of mathematics.
Keywords: Mathematics,Toán học; Miscellanea